2005
DOI: 10.1007/s10549-004-2755-0
|View full text |Cite
|
Sign up to set email alerts
|

The link between the insecticide heptachlor epoxide, estradiol, and breast cancer

Abstract: Given the suspected effects of estrogens on breast cancer, xenoestrogenic insecticides may be a risk factor. Studies of the weak xenoestrogen, 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (DDE), have failed to demonstrate a causal relationship, though another estrogenic organochlorine insecticide, dieldrin, belonging to the cyclodiene family, has recently been linked to breast cancer. Other cyclodienes such as heptachlor epoxide (HE) and oxychlordane (OC) present in breast tissue have not been evaluated as rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Of the remaining 8 studies, the results were mixed. While 4 studies 163,165,169,170 did not observe an association between OC concentrations, the other 4 studies 164,166,168,171 did observe positive associations.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 92%
See 1 more Smart Citation
“…Of the remaining 8 studies, the results were mixed. While 4 studies 163,165,169,170 did not observe an association between OC concentrations, the other 4 studies 164,166,168,171 did observe positive associations.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 92%
“…In our current review, we update the literature since 2002. We identified 11 published studies 32,[162][163][164][165][166][167][168][169][170][171] that reported on associations between measured serum, plasma, or adipose tissue concentrations of OC insecticides and breast cancer, which were not included in either the review by Calle et al or Lopez-Cervantes et al 160,161 Two studies 162,167 were excluded from our review because risk estimates (eg, ORs) were not reported. A third study 32 was excluded because the case definition included prevalent breast cancer.…”
Section: Nonoccupational Oc Insecticide Exposure and Breast Cancermentioning
confidence: 99%
“…In addition to tumor promotion-induced endocrine disruption mechanisms, pesticides may be directly or indirectly mutagenic through free radical production (Cassidy et al, 2005) and may cause both tumor initiation and subsequent tumor promotion by inhibiting Gap junctional intercellular communication (GJIC) (Kang et al, 1996). Inhibition of GJIC has clearly been shown in normal epithelial breast tissue exposed to relatively high concentrations of organochlorine pesticides.…”
Section: Pesticides As Tumor Initiatorsmentioning
confidence: 99%
“…However, there have been conflicting reports on the relationship between exposure to low levels of POPs, such as those occurring in the general population, and cancer risk, with some studies reporting positive associations but many others finding no evidence to support a causal association (Cassidy et al, 2005;Charlier et al, 2003;Cohn et al, 2010;Gatto et al, 2007;Govett et al, 2011;Hardell et al, 2006;Hoyer et al, 2001;Laden et al, 2001;Lopez-Carrillo et al, 2002;Lopez-Cervantes et al, 2004;Mozzachio et al, 2008;Pavuk et al, 2004;Recio-Vega et al, 2011;Snedeker, 2001;Soto and Sonnenschein, 2010;Svensson et al, 1995;Ward et al, 2000;Wolff et al, 2000;Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%